2005
DOI: 10.1255/jnirs.537
|View full text |Cite
|
Sign up to set email alerts
|

Prediction by near Infrared Spectroscopy of the Composition of Plant Raw Materials from the Organic Fertiliser Industry and of Crop Residues from Tropical Agrosystems

Abstract: The dynamics of carbon (C) and nitrogen (N) of plant residues and organic fertilisers are of great interest for agricultural and global warming studies. The proportion of the fractions obtained from biochemical analyses (fibres by sequential Van Soest analysis) can be used for predicting both C and N transformation of organic materials in soils. Considering the expensive and time-consuming Van Soest method, the principal aim of this study was to elaborate near infrared (NIR) calibrations for fibres, in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
(102 reference statements)
3
16
2
1
Order By: Relevance
“…Bruun et al (2005) found that NIR spectra and biochemical fractions were able to predict C mineralization patterns of plant materials equally well. However, when comparing NIR spectra of various materials, Thuriès et al (2005) showed that different models have to be constructed for crop residues and other EOMs.…”
Section: Discussionmentioning
confidence: 99%
“…Bruun et al (2005) found that NIR spectra and biochemical fractions were able to predict C mineralization patterns of plant materials equally well. However, when comparing NIR spectra of various materials, Thuriès et al (2005) showed that different models have to be constructed for crop residues and other EOMs.…”
Section: Discussionmentioning
confidence: 99%
“…NIR studies on plant materials (forages, litters, etc. ), which were developed earlier than on soils, often involve the determination of average spectra using several sub-samples, probably because plant samples are rather hard to grind and are not fi nely ground in general (for example, 1 mm preparation [29][30][31] ). Nevertheless, single NIR measurement was reported with rather fi nely ground plant samples (0.5 mm preparation 32 ).…”
Section: Infl Uence Of Replicationmentioning
confidence: 99%
“…routine. L'erreur de prédiction (SEP) sur le NDF est de l'ordre de 1,50 % de la MS (Andueza et al, 2016) mais peut être plus élevée dans des bases d'étalonnage très hétérogènes (plusieurs espèces végétales ou mélanges ; par exemple Thuriès et al, 2005). L'erreur de prédiction sur l'ADF est généralement inférieure de 30 % à celle du NDF en valeur absolue, mais elle est plus forte en valeur relative (coefficient de variation) car les teneurs en NDF sont supérieures à l'ADF.…”
Section: Paramètre Erreur De Prédiction (Sep Ou Secv) Commentairesunclassified